Binge drinking triggers VGLUT3-mediated glutamate secretion and subsequent hepatic inflammation by activating mGluR5/NOX2 in Kupffer cells - Keungmo Yang; Kyurae Kim; Tom Ryu; Young-Ri Shim; Hee-Hoon Kim; Sung Eun Choi; Min Jeong Kim; Katherine Po Sin Chung; Eunmi Lee; Kwang Woo Lee; Jehwi Jeon; Pilhan Kim; et al. (Nature Communications)
Abstract Glutamate, a crucial player in hepatic amino acid metabolism, has been relatively unexplored in immune cell activation. We show in a study with male mice that hepatic glutamate accumulates in vesicles of perivenous hepatocytes through vesicular glutamate transporter 3 (VGLUT3), regulated by the aryl hydrocarbon receptor upon chronic alcohol intake. Additional binge drinking triggers the exocytosis of glutamate by altering the intracellular Ca2+ level, stimulating metabotropic glutamate receptor 5 (mGluR5) and subsequent NADPH oxidase 2 (NOX2)-mediated ROS production in Kupffer cells (KCs). This interaction between hepatocytes and KCs is facilitated by pseudosynapse formation, arising from alcohol-induced ballooning of perivenous hepatocytes. Genetic or pharmacological interference of mGluR5 or NOX2 in KCs alleviates alcohol-related steatohepatitis (ASH). Analysis of patient samples confirmed some of the findings from mice, showing that plasma glutamate concentration and VGLUT3 levels correlate with ASH development. Conclusively, our findings highlight glutamate storage and release in mediating ASH, particularly through the pseudosynapse between hepatocytes and KCs.